Pengaruh Brand Image, Kualitas Produk, dan Sosial Media Marketing terhadap Keputusan Pembelian di Kopi Analogi Kota Banda Aceh - Iklima Zuhra; Suryani Murad; Ikbal Ramzani (CV. ALIM'SPUBLISHING, 2026)
Competition in the coffee shop industry in Banda Aceh has continued to intensify along with the growing consumer preference for product quality, strong brand image, and the effectiveness of digital marketing through social media platforms. In this context, consumer purchase decisions serve as an important indicator to evaluate the success of the marketing strategies implemented. This study aims to analyze the influence of Brand Image, Product Quality, and Social Media Marketing on consumer Purchase Decisions at Kopi Analogi in Banda Aceh. This research employed a quantitative approach using an associative method. The sample consisted of 83 respondents selected through purposive sampling, with criteria including consumers who had made purchases at Kopi Analogi and were active social media users. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results revealed that Brand Image had a positive and significant influence on Purchase Decisions (t = 3.629; sig. = 0.001). Product Quality also showed a significant effect (t = 2.186; sig. = 0.033), as did Social Media Marketing (t = 4.541; sig. = 0.000). Simultaneously, the three variables had a significant influence on Purchase Decisions (F = 23.978; sig. = 0.000). The coefficient of determination (R²) was 0.564, indicating that 56.4% of the variation in Purchase Decisions could be explained by the three independent variables. The implication of this study suggests that business actors should strategically manage their brand image, maintain consistent product quality, and optimize the use of social media to enhance consumer purchase intention.